Utilization of Digital Drawing Program With Hand Tracking Using the Mediapipe Framework - Jovita Nabilah Azizi; Ester Olivia Silalahi; Rafli Damara; Muhammad Farhan Fahrezy; Fikri Saputra; Gema Parasti Mindara; Endang Purnama Giri (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research focuses on the use of hand tracking technology in a drawing program based on the MediaPipe framework. The aim of this study is to develop a digital drawing system that can track hand movements in real-time without additional input devices like a mouse or stylus. This technology utilizes computer vision algorithms to detect and track the user's hand movements, which are then translated into strokes on the screen. The study employs a descriptive-qualitative method with a software experimentation approach. The results show that the system has a high level of accuracy and is responsive to hand movements, providing a more natural and intuitive user experience. The implications of this research are significant in supporting technology-based educational and creative applications.